Gregor and the code of claw - Collins, Suzanne (New York : Scholastic ; Enfield : Publishers Group UK [distributor], 2008)
When twelve-year-old Gregor finally learns the ancient prophecy, which foretells his death, he must gather his courage to defend Regalia from the army of rats, take his mother and sister home safely, and fight his own dark side.
Keywords: Gregor (Fictitious character : Collins) -- Juvenile fiction; Brothers and sisters -- Juvenile fiction